Evidence of fungal structures in the mandible and elytra ofHypocryphalus mangiferaecollected from mango trees showing symptoms of mango sudden decline disease - Pereira, Rogerio Machado; Martins, Gustavo Ferreira; Silva, Ricardo Siqueira da; Silva Galdino, Tarcisio Visintin da; Ferreira, Dalton de Oliveira; Hector Flechtmann, Carlos Alberto [UNESP]; Picanco, Marcelo Coutinho (Taylor & Francis Ltd, 2020)
Ceratocystis fimbriataplays a significant role in the initiation of the tree decline disease in mango (Mangifera indicaL.), which can kill the plant. TheC. fimbriatainfection is linked with the presence of the beetleHypocryphalus mangiferae(Curculionidae: Scolytinae). However, it is unknown howH. mangiferaeaids in the transport of the fungus between mango trees. The present study aimed to investigate the external surface ofH. mangiferaeadults using scanning electron microscopy to detect signs of the fungus. Fungal structures were found to adhere to the mandible and elytra ofH. mangiferae, implying thatH. mangiferae, while moving between mango trees, may spread the fungus through contact. Our findings may be useful in developing strategies to minimize the economic impact caused by diseases through the control of beetles in mango orchards.
Keywords: Insect-fungus associations; mango sudden decline disease; mango bark beetle; fungal structures; insect dissemination